Content Validity of the Credibility and Expectancy Questionnaire in a Pain Rehabilitation Setting. Issue 7 (30th December 2016) - Mertens, Vera‐Christina; Moser, Albine; Verbunt, Jeanine; Smeets, Rob; Goossens, Mariëlle
Abstract: Background: Content validity, the proper reflection of the concept to be measured, is yet unknown for the Credibility and Expectancy Questionnaire (CEQ). It is frequently used in pain rehabilitation because treatment expectancy is influential on the outcome. Objective: To test and improve the content validity of the CEQ in a sample of patients with chronic pain in different phases of their treatment. Methods: A qualitative observational study design using the Three‐Step Test‐Interview method was used. Therein, data collection, analyses, and adaptations occur iteratively. Results: Seventeen patients with chronic pain in different stages of treatment participated through convenience sampling from the mother sample of a randomized controlled trial. The main study parameter is content validity, which is defined as (1) interpretations and responses of the participants and (2) the identification of response problems operationalized, and resulting in changes in the CEQ. For patients waiting for treatment, the written instruction of the CEQ allowed different interpretations. After changing the instructions, the CEQ became an easy‐to‐understand and content‐valid questionnaire. For patients who had already undergone treatment, changes regarding time frame and recall period were necessary to overcome interpretation and response problems to the CEQ. Discussion: After small changes, the CEQ appeared to be a content‐valid measurement instrument for patients waiting for treatment. However, for patients who had already undergone treatment, the content validity of the CEQ was less, and considerable changes were necessary.